The effect of nutrition education sessions on energy availability, body composition, eating attitude and sports nutrition knowledge in young female endurance athletes - Cansu Tektunalı Akman; Canan Gönen Aydın; Gülgün Ersoy (Frontiers Media S.A., 2024)
Nutrition knowledge plays a pivotal role in shaping dietary habits and food choices, particularly in the realm of sports nutrition. This study investigates the effects of a series of nutrition education sessions conducted by a registered dietitian on energy availability, various anthropometric measurements, eating attitudes, and sports nutrition knowledge in young female endurance athletes aged 15-18 years (football, basketball, volleyball) who engage in training for more than 10 h per week (n = 83). Participants were randomly divided into two groups with 45 individuals receiving six physical nutrition education lectures, and the remaining 38 participants receiving no nutrition education. Participants completed the low energy availability in females questionnaire (LEAF-Q), Eating Attitude Test (EAT-26), and Sports Nutrition Knowledge Questionnaire (SNKQ). Energy and nutrient intakes were evaluated through 3-day food records, while exercise energy expenditure was assessed using 3-day activity logs. All of the questionnaires were repeated after 6 months. At baseline, the prevalence of LEA among athletes was determined to be 63.8%. In the intervention group, energy availability (EA) and SNKQ scores increased, and LEAF-Q scores decreased significantly (p < 0.05). However, there was no significant change in EAT-26 scores between the two groups. Energy intake, weight, fat-free mass, and resting metabolic rate have been increased significantly in the intervention group (p < 0,05). These findings suggest that nutrition education proves beneficial in enhancing dietary intake, positively influencing body composition, and improving nutrition knowledge, ultimately contributing to increased energy availability in female athletes over the short term.